Emphysema formation in a never-smoker with scleroderma-related interstitial pneumonia. (2018) - Yamakawa, Hideaki; Takemura, Tamiko; Baba, Tomohisa; Ogura, Takashi
Abstract: We report a case of pathological emphysema formation in a never-smoker with scleroderma-related interstitial pneumonia. We realized the importance of pulmonary vasculopathy causing the coexistence of emphysema and fibrosis in scleroderma. Our discovery provides novel information that emphysema can occur in patients with scleroderma-related interstitial pneumonia who have never smoked.